Complicações micro e macrovasculares em pessoas com Diabetes Mellitus tipo 2 em atendimento ambulatorial - Valéria Cristina Delfino de Almeida; Samila Torquato Araújo; Francisca Diana da Silva Negreiros; Maria Isis Freire de Aguiar; Tatiana Rebouças Moreira; Ana Paula Plácido Crispim (Universidade Federal do Ceará, 2017)
Objective: to analyze the factors related to micro and macro vascular complications in people with type 2 diabetes mellitus. Methods: a documentary survey of 134 patients with type 2 diabetes mellitus. Bivariate statistical analysis (Pearson's Chi-square test and Fisher's test), with statistical significance if p<0.05. Results: the frequency of micro vascular complications was 50.7%, and retinopathy was the most found (61.7%). There was a statistical association between the group with more than 10 years of disease and the presence of retinopathy. Cardiopathy was one of the most frequent macro vascular complications (69.0%). Regarding the use of insulin therapy in mono therapy, there was significance in the presence of nephropathy and vascular disease. Conclusion: results with statistical significance related to the appearance of complications with disease time, highlighting the presence of diabetic retinopathy. It was verified that the lower the schooling, the greater the onset of vascular disease.